2010
DOI: 10.1007/s11270-010-0331-2
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Landsat-5TM Image Data for Water Quality Mapping in Lake Beysehir, Turkey

Abstract: The main goal of this study was to investigate spatial patterns in water quality in Lake Beysehir, which is the largest freshwater reservoir in Turkey, by using Landsat-5TM (Thematic Mapper) data and ground surveys. Suspended sediment (SS), turbidity, Secchi disk depth (SDD), and chlorophyll-a (chl-a) data were collected from 40 sampling stations in August, 2006. Spatial patterns in these parameters were estimated using bivariate and multiple regression (MR) techniques based on Landsat-5TM multispectral data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 29 publications
0
48
0
2
Order By: Relevance
“…Some studies have demonstrated that the ratios (band 3)/(band 1) and (band 2)/(band 1) best correlate with in situ measurements of turbidity (Nas et al, 2010;Raharimahefa & Kusky, 2010). The turbidity index used in this study is thus the sum of the two ratios in a way that considers the spectral ranges where turbidity best correlates:…”
Section: Characterisation Of Turbidity and Chlorophyll-amentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies have demonstrated that the ratios (band 3)/(band 1) and (band 2)/(band 1) best correlate with in situ measurements of turbidity (Nas et al, 2010;Raharimahefa & Kusky, 2010). The turbidity index used in this study is thus the sum of the two ratios in a way that considers the spectral ranges where turbidity best correlates:…”
Section: Characterisation Of Turbidity and Chlorophyll-amentioning
confidence: 99%
“…However, the development of such models depends on the availability of in situ data to correlate with reflectance on the time of satellite overpass (Hadjimitsis et al, 2006;Nas et al, 2010). Again, the models are very diverse and specific to the reservoirs studied, which makes them not replicable elsewhere.…”
Section: Characterisation Of Turbidity and Chlorophyll-amentioning
confidence: 99%
See 3 more Smart Citations